2020
DOI: 10.3390/ijms21197265
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Mediates Cholesterol Efflux Impairment in Macrophages Caused by Human Advanced Glycated Albumin

Abstract: We addressed the involvement of the receptor for advanced glycation end products (RAGE) in the impairment of the cellular cholesterol efflux elicited by glycated albumin. Albumin was isolated from type 1 (DM1) and type 2 (DM2) diabetes mellitus (HbA1c > 9%) and non-DM subjects (C). Moreover, albumin was glycated in vitro (AGE-albumin). Macrophages from Ager null and wild-type (WT) mice, or THP-1 transfected with siRNA-AGER, were treated with C, DM1, DM2, non-glycated or AGE-albumin. The cholesterol efflux w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In human umbilical vascular endothelial cells, human glycated albumin differentially regulates proteins involved in endothelial dysfunction, namely related to apoptosis and oxidative stress and the NF-KB cascade downstream to AGE-RAGE signaling, which can be counteracted by soluble RAGE [ 23 ]. The deleterious effects of AGE-albumin in cholesterol homeostasis are mediated by RAGE—a highly expressed multi-ligand receptor in atherosclerotic plaques—since they were not observed in macrophages from RAGE knockout mice [ 24 ]. In another study, BMDMs from mice with DM presented a reduced cholesterol efflux to apoA-I and HDL, as compared to BMDMs from control animals.…”
Section: Discussionmentioning
confidence: 99%
“…In human umbilical vascular endothelial cells, human glycated albumin differentially regulates proteins involved in endothelial dysfunction, namely related to apoptosis and oxidative stress and the NF-KB cascade downstream to AGE-RAGE signaling, which can be counteracted by soluble RAGE [ 23 ]. The deleterious effects of AGE-albumin in cholesterol homeostasis are mediated by RAGE—a highly expressed multi-ligand receptor in atherosclerotic plaques—since they were not observed in macrophages from RAGE knockout mice [ 24 ]. In another study, BMDMs from mice with DM presented a reduced cholesterol efflux to apoA-I and HDL, as compared to BMDMs from control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mRNA expression of RAGE was not affected by addition of sRAGE to CRP in comparison to CRP alone in both models (data not shown) indicating that effects of sRAGE seemed to be restricted to the functional level of RAGE. In this context, it was shown that RAGE can mediate uptake as well as efflux transport processes [ 48 , 49 ]. In relation to our results, it could be speculated that RAGE mediates the uptake of CRP into saliva across the oral mucosa epithelium, whereas it is involved in efflux mechanisms to restrict exorbitant accumulation of CRP in saliva via the salivary gland epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin was isolated from patients with type 1 and type 2 diabetes (T1D and T2D, respectively) and from non-diabetic control subjects. Macrophages were retrieved from Ager null and wild-type mice, or human THP1 cells were subjected to treatment with silencing RNAs to reduce the expression of AGER [ 63 ]. Compared to wild-type murine macrophages and control-treated THP1 cells, cholesterol efflux was reduced in response to albumin from T1D or T2D patients vs control albumin [ 63 ]; in parallel with increased intracellular lipid content.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages were retrieved from Ager null and wild-type mice, or human THP1 cells were subjected to treatment with silencing RNAs to reduce the expression of AGER [ 63 ]. Compared to wild-type murine macrophages and control-treated THP1 cells, cholesterol efflux was reduced in response to albumin from T1D or T2D patients vs control albumin [ 63 ]; in parallel with increased intracellular lipid content. These effects of the human diabetic albumin were reduced in macrophages lacking Ager; in that setting, cholesterol efflux and lipid staining were higher and lower, respectively, when compared to the control RAGE-expressing cells [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation